Mediating Role of Motivation on the Relationship between Competency Gap and Training Experience on Employee Performance: A Literature Review - Muhammad Zeinny Hasbunallah Sasmita; Aep Syaefullah; Tiara Mustika Ayu; Zia Majiatul Arobiah; Aulia Nur’aini; Elty Sukaesih; Euis Huzaziah; Andre Genta Sanjaya (PT Ilmu Data Indonesia, 2026)
This study examines the influence of competency gaps and training experience on employee performance, with work motivation serving as a mediating variable. Employing a literature review method, the research draws upon secondary sources including peer-reviewed journals, academic textbooks, and relevant regulatory frameworks. The analytical framework incorporates multiple statistical approaches: Structural Equation Modeling (SEM) to assess causal relationships and mediation effects, Moderated Regression Analysis (MRA) processed through SPSS software, linear regression to determine direct effects, and Path Analysis to differentiate impacts across specific categories. The findings reveal that competency gaps impede performance optimization; however, this hindrance can be mitigated through needs-based training interventions and enhanced work motivation. The study recommends strengthening demand-driven training systems, conducting periodic competency evaluations, and formulating policies that foster work motivation to optimize employee performance. The theoretical contribution of this research enriches the discourse on civil servant competency development and advocates for an integrated approach to training and motivation policies.